2018
DOI: 10.1029/2018wr023160
|View full text |Cite
|
Sign up to set email alerts
|

A Clustering Preprocessing Framework for the Subannual Calibration of a Hydrological Model Considering Climate‐Land Surface Variations

Abstract: One model structural deficiency is that some dynamic characteristics (such as seasonal dynamics) in catchment conditions are not explicitly represented by hydrological models. This study integrates data mining techniques to develop a clustering preprocessing framework for the subannual calibration of hydrological models to simulate seasonal dynamic behaviors. The proposed framework aims to solve the problems caused by missing processes and deficiencies of hydrological models, providing guidance for future mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…Hence, seasonal climate variability is the main cause of the nonstationarity in the hydrological processes of the Xun River basin. This finding is in agreement with the work of Lan et al (2018), who also recognized and analyzed the seasonal hydrological dynamics of this study region.…”
Section: / 58supporting
confidence: 93%
“…Hence, seasonal climate variability is the main cause of the nonstationarity in the hydrological processes of the Xun River basin. This finding is in agreement with the work of Lan et al (2018), who also recognized and analyzed the seasonal hydrological dynamics of this study region.…”
Section: / 58supporting
confidence: 93%
“…Climatically, the Han Jiang basin is located in the monsoon region of the eastern Asia subtropical zone. The area is cold and dry in winter and warm and humid in summer (Lin et al, 2010), and there are seasonal changes in vegetation density and types (Fang et al, 2002). Subtropical vegetation affects temporal moisture con-ditions.…”
Section: Study Cases and Datamentioning
confidence: 99%
“…Therefore, the effects of the "compensation" between the parameters on the dynamics of hydrological model parameters are investigated using a control scheme i.e., Scheme 2. The most common approach for assessing the dynamics of the hydrological model parameters is that the calibration period is partitioned into different sub-periods based on the temporal dynamic catchment characteristics (Sarhadi et al, 2016;Merz et al, 2011;Lan et al, 2018;Xiong et al, 2019;Motavita et al, 2019;Deng et al, 2018;Dakhlaoui et al, 2017;Choi and Beven, 2007;Brigode et al, 2013;Kim et al, 2015;Kim and Han, 2017;Zhao et al, 2017;Pfannerstill et al, 2015;Me et al, 2015;Deng et al, 2016;Coron et al, 2014;Vormoor et al, 2018;Luo et al, 2012;Guse et al, 2016;Zhang et al, 2015;Ouyang et al, 2016;Zhang et al, 2011). The parameter set in each sub-period is optimized to obtain the dynamic parameter set.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that sub-period calibration based on the dynamic catchment behaviour accurately captures the temporal variations of the catchment characteristics, thereby compensating for structural inadequacy (Lan et al, 2018;Zhao et al, 2017;Kim and Han, 2017;Zhang et al, 2011;De Vos et al, 2010;Gupta et al, 2009;Choi and Beven, 2007;van Griensven et al, 2006;Freer et al, 2003). In the study of Choi and Beven (2007), the sub-periods were identified based on different hydrological characteristics using a clustering technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation